Do soccer players with superior implicit pattern perception process soccer situations emotionally? - Murakawa, D.; Ikudome, S.; Kamei, M.; Mori, S.; Nakamoto, H. (Japanese Journal of Sport Psychology, 2021)
Recently, it was reported that superior soccer decision-makers possess better implicit pattern perception (Murakawa et al., 2020). However, it is unclear how such excellent implicit pattern perception is achieved. Therefore, in this study, we examined the possibility that soccer players with excellent implicit pattern perception emotionally process scenes with an unmarked player around the goal. Twenty-eight skilled soccer players performed a task based on the backward-masking paradigm used by Murakawa et al. (2020) to assess the accuracy of implicit pattern perception for soccer 3-on-3 scenes around the goal. Eleven of the 28 participants performed the task newly and for 17 individuals, the data of Murakawa et al. (2020) were reused. In addition, using a subliminal priming task, we evaluated participants' impressions (pleasant/unpleasant) about a target stimulus (Arabic) that was presented following implicitly perceived images of a 3-versus-3 scene (goal/free condition, goal/no-free condition, no-goal/free condition, no-goal/no-free condition) around the goal. Under the goal/free condition, offensive players with high accuracy of implicit pattern perception were biased toward pleasant, and defensive players were biased toward unpleasant. On the other hand, no such bias was observed under the no-goal/no-free condition. Thus, this suggests that players with better implicit pattern perception perform emotional perceptual processing of environmental information based on the emotional value arising from his/her knowledge base. It is significant that our study is the first to provide evidence for the relationship between emotional processing and implicit pattern perception, involved in superior decision-making in soccer.